Unravelling the key role of surface features behind facet-dependent photocatalysis of anatase TiO2 - Peng, Y-K; Keeling, B; Li, Y; Zheng, J; Chen, T; Chou, H-L; Puchtler, TJ; Taylor, RA; Tsang, SCE (Royal Society of Chemistry, 2019)
The high activity of nanocrystallites is commonly attributed to the terminal high-energy facets. However, we demonstrate that the high activity of the anatase TiO2(001) facet in photocatalytic H2 evolution is not due to its high intrinsic surface energy, but local electronic effects created by surface features on the facet.